Temporal resolution assessment in cochlear implant recipients using an auditory gap detection test - Binos, Paris (My University, 2019)
To explore the role of GIN test as a valuable diagnostic tool for the assessment of temporal resolution ability of individuals wearing cochlear implants and the endeavors at increasing the transmission of TFS to CI users based on literature findings.
Keywords: temporal resolution; cochlear implant; gap detection test; deaf; hearing impairment; diagnosis